ANALISIS SISTEM PRODUKSI DENGAN PENDEKATAN LEAN MANUFACTURING UNTUK MENINGKATKAN PRODUKTIVITAS DI PT. PANAMAS MITRA INTI LESTARI - Mohammad Cipto Sugiono (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari Banjarmasin, 2022)
PT. Panamas Mitra Inti Lestari is a company engaged in the production of household appliances, which need to continually improve productivity performance to increase the maximum profit by trying to reduce costs, improve quality and timely delivery to customers. In conducting the production process there is a discrepancy of the output of production with a production target specified. This happens because it was discovered their waste in the production process. Waste prioritized for attention in the production process is waste of defect and transportation. Therefore we need a lean manufacturing approach. The first thing to do is to identify the waste that occurs by creating a current state map, waste on the current state map and look for the root cause analysis using fishbone diagram analysis and FMEA. Recommendations for improvements in future state mapping is implementing continuous flow by reducing WIP at the work station is the shortest cycle time. After being given the proposed recommendations for improvement then the last step is to describe the future state map and analyze the changes that occur so that the results obtained are reduced lead time for (28.44%), a reduction in total inventory (28.50%). The decline in total travel time (2.65%) and the last is the reduction of travel distance (7.95%). Keywords: Lean Manufacturing, Value Stream Mapping, Diagram Fishbone Safety Stock